The puzzle assembled: Ediacaran guide fossil Cloudina reveals an old proto-Gondwana seaway - Warren, L. V. [UNESP]; Quaglio, F. [UNESP]; Riccomini, C.; Simoes, M. G. [UNESP]; Poire, D. G.; Strikis, N. M.; Anelli, L. E.; Strikis, P. C. (Geological Soc Amer, Inc, 2014)
During the Ediacaran the Clymene Ocean separated the Laurentia, Amazonia, and Rio Apa cratons from several landmasses to the west forming the proto-Gondwana supercontinent. However, no clear evidence about the existence of Ediacaran epeiric seas over those landmasses has been found. Here we report and discuss the discovery of the Ediacaran guide fossil Cloudina sp. associated with other metazoan body and trace fossils in the Bambu Group (central eastern Brazil). The Ediacaran age of the Bambu Group and the paleogeographic position of Cloudina-bearing successions in Brazil, Antarctica, Namibia, and Argentina suggest a scenario of ocean connectivity among coeval intracratonic basins of South America, Africa, and Antarctica at the end of Neoproterozoic time. The new finding epitomizes one of the most important paleontological discoveries ever made in South America, helping to solve an old paleogeographic puzzle of the Gondwana supercontinent.